2018
DOI: 10.3389/fendo.2017.00383
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolic Syndrome and Its Components in African-American Women: Emerging Trends and Implications

Abstract: The Metabolic Syndrome (MetS) is recognized as a predictor of cardiovascular outcomes and type 2 diabetes (T2DM). The MetS is a constellation of clinical and metabolic risk factors that include abdominal obesity, dyslipidemia, glucose intolerance, and hypertension. There are ethnic and racial differences in the prevalence of MetS and its components. In general, African-Americans have lower prevalence of MetS when compared to whites, but suffer disproportionately from higher cardiovascular mortality and T2DM. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 69 publications
1
16
0
2
Order By: Relevance
“…Obesity is de ned as the excessive accumulation and/or abnormal distribution of fat in the body. It is a chronic metabolic disease caused by the interaction of genetic and environmental factors [1,24]. A large number of studies have shown that STAU1 can regulate cell growth and nerve differentiation [25].…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is de ned as the excessive accumulation and/or abnormal distribution of fat in the body. It is a chronic metabolic disease caused by the interaction of genetic and environmental factors [1,24]. A large number of studies have shown that STAU1 can regulate cell growth and nerve differentiation [25].…”
Section: Discussionmentioning
confidence: 99%
“…According to the NHANES ((National Health and Nutrition Examination Survey) dataset, AAs had one of the lowest mean TG compared to Caucasian and Mexican Americans [7]. Moreover, studies have shown that AAs with insulin resistance have been found to have lower TG and higher HDLC as compared to Caucasians [8]. Serum lipids play a substantial role as a predictive biomarker in cardiometabolic disease and as a result of this more favorable lipid profile among AAs, it would be Volume: reasonable to assume that T2DM among AAs would be less prevalent, however from an epidemiological standpoint, this is not the observed [7].…”
Section: Serum Lipids Paradox Among African Americansmentioning
confidence: 99%
“…Metabolic Syndrome (MetS) is a constellation of clinical and metabolic risk factors that include abdominal obesity, dyslipidemia, glucose intolerance, and hypertension. In general, blacks have lower prevalence of MetS when compared to whites, but suffer disproportionately from higher cardiovascular mortality and type two diabetes mellitus [12]. It is unclear whether OSA and metabolic syndrome work synergistically within the black population to place this vulnerable sub-group at an even greater risk of stroke.…”
mentioning
confidence: 99%